Impact of Social Media Marketing and Service Quality on Engagement and Purchase Intention at Moria Café - Zeffry, Zeffry; Bernard T. Widjaja (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study aims to analyze the influence of Social Media Marketing (SMM) and Service Quality (SQ) on Customer Engagement (CE) and Purchase Intention (PI) among customers of Moria Coffee, a growing local coffee shop in Lembang, West Java. A quantitative approach was employed using Structural Equation Modeling Partial Least Squares (SEM-PLS), processed with SmartPLS 4 software. Data were collected from 160 respondents using a closed-ended questionnaire with a Likert scale. This study employs a quantitative approach using an explanatory survey method. The quantitative approach was chosen as it allows for the collection of numerical data that can be statistically analyzed to objectively and systematically examine causal relationships between research variables. : The findings show that SMM does not directly influence PI but has a significant effect on CE. Conversely, SQ directly and significantly affects both CE and PI. Furthermore, CE is proven to mediate the relationship between both SMM and PI, and SQ and PI. The R-square values indicate strong predictive power (R² PI = 0.671), and PLS Predict results confirm that the model has a reliable predictive capability for new data. These results underscore the strategic role of Customer Engagement as a mediator between external marketing stimuli and consumers’ purchase intention. The study offers practical implications for digital marketing management and service strategies, as well as theoretical contributions to consumer behavior literature focusing on engagement and experiential marketing